Language networks : the new word grammar - Hudson, Richard A. (Oxford linguistics., 2007)
This book presents a new theory of how we learn and use our knowledge of language and puts this to work in explorations of morphology, syntax, semantics, and sociolinguistics. It introduces the latest version of the author's influential theory of Word Grammar and shows how it can be used to explain the operations of language and as a key to understanding the associated operations of the mind. Language Networks will interest all those concerned with the acquisition and. workings of language. - ;This book argues that language is a network of concepts which in turn is part of the general cognitiv.